Controversial Issues of Hydrocarbon Field Formation and the Role of Geomagnetic Fields - Andrey A. Ponomarev; Marsel A. Kadyrov; Yuri V. Vaganov; Valeria A. Cheymetova; Vadim M. Aleksandrov; Aleksandr V. Morev (International Journal of Geophysics)
This review paper presents controversial issues on the formation of hydrocarbon deposits. We look into the geological contradictions of the abiogenic and biogenic theories of petroleum origin, indicating the connection between hydrocarbon deposits and disjunctive dislocations, as well as present disputes about the geological period over which hydrocarbon deposits have been formed. We further overviewed the radical chain mechanism of hydrocarbon generation from organic matter as proposed by Prof. Nesterov. It is noted that the petroleum generation process in reservoir conditions occurs almost instantly in the presence of discrete geomagnetic fields and does not require a long geological time. This is explained by spin magnetic effects (spin catalysis, magnetic isotope properties). We briefly highlight the effect of magnetic fields on chemical reactions involving organic compounds and the use of magnetic fields to enhance oil recovery. We also present the leading causes of discrete magnetic fields in the sedimentary cover: Earth’s geomagnetic reversals, generation of ferromagnetic minerals in oil deposits, electromechanical effects of rock friction near faults, and intermixing of reservoir waters with different mineralization (spontaneous ion polarization). Based on the material reported, we conclude that the radical chain mechanism of petroleum generation processes explains some contradictions of the abiogenic and biogenic theories of petroleum origin. Elaborating this research area has excellent prospects for developing new criteria for hydrocarbon prospecting and devising innovative methods to enhance the oil recovery for shale oil production.